2013
DOI: 10.7567/apex.6.112601
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Tetragonal InBi Clusters in InAsBi/InAs(100) Heterostructures Grown by Molecular Beam Epitaxy

Abstract: This work analyses the Bi incorporation in InAs1-xBix/InAs(100) epilayers grown by MBE through advanced transmission electron microscopy techniques. Samples grown from 350–400 °C resulted in Bi contents <3.3% exhibiting compositional variation in the growth direction. In contrast, roughly spherical clusters appeared in the sample grown at lower temperatures. The clusters are made up of the binary InBi with a tetragonal PbO phase surrounded by a matrix of InAs0.95Bi0.05 indicating the Bi solubility limit in InA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…EDX analysis performed on various droplet positions indicates that the droplet consists predominantly of Bi. In comparison, Bi-rich zincblende Ga(As, Bi) clusters and rhombohedral Bi clusters were reported for GaAsBi after annealing [21], and InBi clusters with distorted PbO structure were reported in InAsBi [22]. Such phase separation is attributed to the difficulties associated with Bi incorporation.…”
Section: Inas 1 à X Bi X Alloysmentioning
confidence: 93%
See 1 more Smart Citation
“…EDX analysis performed on various droplet positions indicates that the droplet consists predominantly of Bi. In comparison, Bi-rich zincblende Ga(As, Bi) clusters and rhombohedral Bi clusters were reported for GaAsBi after annealing [21], and InBi clusters with distorted PbO structure were reported in InAsBi [22]. Such phase separation is attributed to the difficulties associated with Bi incorporation.…”
Section: Inas 1 à X Bi X Alloysmentioning
confidence: 93%
“…Microstructural studies done on epitaxial GaAs 1À x Bi x films grown by molecular beam epitaxy (MBE) have shown that the film morphology departs from homogeneity in several ways, including phase separation [5], atomic ordering [5,6] and surface-droplet formation [7], despite all the efforts directed towards optimizing the growth. In comparison, the growth of InAs 1À x Bi x alloys by MBE has only recently been established [8][9][10], and there is a need for detailed microstructural study of such alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Further deposit of Bi atoms on surface leads to droplet coalescence. In reference [123], the droplet coalescence process was explained by Ostwald ripening [124]. Formation of Bi droplets indicates that it is a thermodynamically driven process.…”
Section: Bi Dropletsmentioning
confidence: 99%
“…In 2012, InBi crystals were initially grown by Dominguez et al [124] using MBE growth. In their study, Bi incorporation in InAsBi/InAs (100) is analyzed through advanced TEM techniques.…”
Section: Epitaxial Growth Of Inasbimentioning
confidence: 99%
“…theoretically analyzed InSbBi, InAsBi and InPBi as potential candidates for mid- and far-infrared (IR) optoelectronics applications in 1988 and pointed out that InSbBi was the easiest and InPBi was the most difficult to mix, but once formed, InPBi was the hardest among the three materials 11 , making it an attractive narrow-gap material candidate. Since InBi crystallizes in the tetragonal PbO-type structure rather than the cubic zinc-blende structure common for semiconducting III–V compounds, the mixing of InBi with other materials of zinc-blende structure may lead to problems 12 . Early work by Oe et al .…”
mentioning
confidence: 99%